The influence of culture on organizational change / Wan Hanisah Wan Ismail - Wan Ismail, Wan Hanisah (Universiti Teknologi MARA Cawangan Pahang, 2005)
Change is an inevitable process. UiTM being one of the biggest universities in the country, is experiencing tremendous change in responses to the globalization of the education sector. However, organizational change is intimately tied up to the culture of the people within the organization. The success or failure of any change effort may be influenced by the existing culture. Changing the organization needs to be accompanied by change in existing culture. Therefore it is very important for managers to first understand the existing culture and, then, identify the changes that need to be brought forward.